Before you do : making great decisions that that you won't regret - Jakes, T. D. (New York, NY : Atria Books, 2008)
Relationship decisions come down to five crucial components, according to Bishop Jakes: Research--gathering information and collecting data; Roadwork--removing obstacles and clearing the path; Rewards--listing choices and imaging their consequences; Revelation--narrowing your options and making your selection; Rearview--looking back and adjusting as necessary to stay on course. This book gets you on the right track to making decisions that you'll be proud of and reap the benefits of for the rest of your life, as will the generations that follow you. He gives you insight on how to reflect, discern, and decide the next step to take to have a strong and enduring love, marriage, and family. The Bishop takes a spiritual and practical approach to inherently emotional issues such as the outside influences on our relationships, coping with anger, parenting, financial concerns, negotiating high-profile lives, and more.--From publisher description.
Before you decide -- Before you take the first step : reflect, discern -- Before you blame : accept responsibility -- Before you leave junk in your trunk : clean up emotionally -- Before you lead : decide on your team -- Before you join -- Before you decide to love -- Before you place your love order -- Before you commit : research -- Before you commit : development -- Before you get engaged : 20 final exam questions -- Before you marry -- Before you decide to take a risk for your marriage -- Before you buy a house -- Before you have children -- Before you divorce -- Before you settle for less -- Before you fight -- Before you take flight -- Before you gamble -- Now you've done it.
Keywords: Mate selection; Decision making; Life skills